Prodigiosin Promotes Nrf2 Activation to Inhibit Oxidative Stress Induced by Microcystin-LR in HepG2 Cells - Jihua Chen; Yuji Li; Fuqiang Liu; De-Xing Hou; Jingjing Xu; Xinying Zhao; Fei Yang; Xiangling Feng (Toxins, 2019)
Microcystin-LR (MC-LR), a cyanotoxin produced by cyanobacteria, induces oxidative stress in various types of cells. Prodigiosin, a red linear tripyrrole pigment, has been recently reported to have antimicrobial, antioxidative, and anticancer properties. How prodigiosin reacts to reactive oxygen species (ROS) induced by MC-LR is still undetermined. This study aimed to examine the effect of prodigiosin against oxidative stress induced by MC-LR in HepG2 cells. Ros was generated after cells were treated with MC-LR and was significantly inhibited with treatment of prodigiosin. In prodigiosin-treated cells, the levels of nuclear factor erythroid 2-related factor 2 (Nrf2) and Nrf2-related phase II enzyme heme oxygenase-1 (HO-1) were increased. Besides, prodigiosin contributed to enhance nuclear Nrf2 level and repressed ubiquitination. Furthermore, prodigiosin promoted Nrf2 protein level and inhibited ROS in Nrf2 knocked down HepG2 cells. Results indicated that prodigiosin reduced ROS induced by MC-LR by enhancing Nrf2 translocation into the nucleus in HepG2 cells. The finding presents new clues for the potential clinical applications of prodigiosin for inhibiting MC-LR-induced oxidative injury in the future.